2019
DOI: 10.1002/2211-5463.12709
|View full text |Cite
|
Sign up to set email alerts
|

Profiling and functional analysis of differentially expressed circular RNAs in high glucose‐induced human umbilical vein endothelial cells

Abstract: Dysfunction of vascular endothelial cells often results in diabetic vascular complications. Circular RNAs (circRNAs) have been implicated in the pathogenesis of various diseases, including diabetes and many vascular diseases. This study aimed to explore the roles of circRNAs in high glucose‐induced human umbilical vein endothelial cells (HUVECs) to elucidate the contributions of circRNAs to diabetic vascular complications. We subjected control and high glucose‐induced HUVECs to RNA sequencing and identified 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 64 publications
1
18
0
Order By: Relevance
“…It was reported that circ_CLASP2 expression was prominently decreased in HUVECs under HG exposure (Jin, Wang, 2019). To validate this, we used HG to treat HUVECs for various time points, and our data supported the downregulation of circ-CLASP2 in HG-treated HUVECs.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…It was reported that circ_CLASP2 expression was prominently decreased in HUVECs under HG exposure (Jin, Wang, 2019). To validate this, we used HG to treat HUVECs for various time points, and our data supported the downregulation of circ-CLASP2 in HG-treated HUVECs.…”
Section: Discussionsupporting
confidence: 73%
“…Hence, it is very crucial to identify effective biomarkers for the detection of ECs dysfunction and the prevention of macrovascular complications. One promising biomarker is based on circular RNAs (circRNAs) ( Shang et al, 2018 ; Jin et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CircRNAs are a widespread RNA species in various species and have important biological functions. They are involved in the regulation of islet cell function and insulin metabolism [18], also mediate vascular damage caused by high glucose as well [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Shang et al 24 reported that more than 1,000 new circRNAs and 95 differentially expressed circRNAs were detected in HUVEC cultured in high glucose environment in vitro. Jin et al 25 identified 214 differentially expressed circRNAs in high glucose induced HUVEC compared with normal controls by using RNA sequencing, of which 7 were validated using qPCR (hsa_circ_0008360, hsa_circ_0005741, hsa_circ_0003250, hsa_circ_0045462, hsa_circ_0064772, hsa_circ_0007976 and hsa_circ_0005263). Huang et al 26 reported that in rat HAEC induced by transforming growth factor β1 (TGF-β1), a total of 102 circRNA was differentially expressed, of which 66 circRNA expressions were up-regulated and 26 circRNA expressions were down-regulated.…”
Section: Dysregulated Circrna In Drmentioning
confidence: 99%